Difference between revisions of "Math 22 Derivatives of Exponential Functions"
Jump to navigation
Jump to search
Line 40: | Line 40: | ||
|<math>f(x)=\frac{e^x-e^{-x}}{2}=\frac{e^x}{2}-\frac{e^{-x}}{2}=\frac{1}{2}e^x-\frac{1}{2}e^{-x}</math> | |<math>f(x)=\frac{e^x-e^{-x}}{2}=\frac{e^x}{2}-\frac{e^{-x}}{2}=\frac{1}{2}e^x-\frac{1}{2}e^{-x}</math> | ||
|- | |- | ||
− | |<math>f'(x)=\frac{1}{2}e^x-\frac{1}{2}(-1)e^{-x}</math> | + | |<math>f'(x)=\frac{1}{2}e^x-\frac{1}{2}(-1)e^{-x}=\frac{1}{2}e^x+\frac{1}{2}e^{-x}</math> |
|} | |} | ||
[[Math_22| '''Return to Topics Page''']] | [[Math_22| '''Return to Topics Page''']] | ||
'''This page were made by [[Contributors|Tri Phan]]''' | '''This page were made by [[Contributors|Tri Phan]]''' |
Latest revision as of 07:40, 11 August 2020
Derivative of the Natural Exponential Function
Let be a differentiable function of . Then, 1. 2.
Exercises Differentiate each function:
a)
Solution: |
---|
b)
Solution: |
---|
c)
Solution: |
---|
d)
Solution: |
---|
e)
Solution: |
---|
This page were made by Tri Phan